GENDER QUESTIONS AND ITS IMPLICATIONS FROM BRAZILIAN COLONIZATION PROCESS UNTIL THE XXI CENTURY (Fiep Bulletin - online, 2015)
The Brazilian African American population is beginning to comprehend the necessity of accelerating the process of paradigm break and the secular hindrance confrontation that hinder or raise extreme difficulties to its emancipation and equalization to the white population. However, this battle was initiated more than four Centuries ago with the institution of the black people slavery system. More than a hundred years have passed since the Slavery abolition happened in Brazil, and the insertion of this enormous populational contingent in the Brazilian capitalist civil society and its struggle for the end of the racial discrimination, continues to be a huge challenge to governments that are really interested in this set of problems and for the future generations. The Brazilian Institute of Statistics - Instituto Brasileiro de Geografia e Estatística  IBGE  presents in its reports impressive data related to our people and its ethnic group and the socio-economic conditions/educational conditions in different populational segments. These numbers give us the notion of the poverty situation, the lack of dignity and of the exclusion process that the African American population suffer. The physics education and sports have been one of the most efficient ways for the African American population, not only in Brazil but in many other different countries. Incredible victories like the one from the American runner Jesse Owens in the Olympic Games in 1936, in Berlin, in the presence of the astonished and skeptic Hitler, the exceptional performance and popularity of the gymnast Daiane dos Santos, the excellent basket and volleyball players from our national teams, the great talents of our athletics team as Ademar Ferreira da Silva, João do Pulo, Robson Caetano among others, besides the soccer players like Pelé, Leônidas da Silva and Robinho have been enabling the most needy populational groups access to the so disseminated social inclusion.
Keywords: Gender; interpersonal relations; exclusion.